Chronicles of Narnia. The voyage of the dawn treader - Barnes, Ben, 1981-; Henley, Georgie; Keynes, Skandar; Twentieth Century Fox Home Entertainment, Inc. ([United States] : 20th Century Fox Home Entertainment, 2011)
When Lucy and Edmund Pevensie, along with their cousin Eustace, are swallowed into a painting and transported back to Narnia, they join King Caspian and a noble mouse named Reepicheep aboard the magnificent ship the Dawn Treader. The courageous voyagers travel to mysterious islands, confront mystical creatures, and reunite with the Great Lion Aslan and a mission that will determine the fate of Narnia itself!
DVD, widescreen.
English or French dialogue; French or Spanish subtitles; English subtitles for the deaf and hard of hearing.
Closed-captioned.
Title from container.
Ben Barnes, Georgie Henley, Skandar Keynes.
Release date: Apr. 8, 2011.
Keywords: Narnia (Imaginary place) -- Drama; Feature films; Children's films; Fiction films; Fantasy films; Video recordings for the hearing impaired